Supply Chain Analysis of Green Mussel Business in Umbul Asem Village Bandar Lampung - Sundari, Susanti (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Umbul Asem village is a coastal area has a fairly high potential, especially the farming of green mussels. However, the prospect of green mussel farming which is quite large is still not realized by all fishermen so it is necessary to conduct research to determine the green mussel supply chain and see what opportunities from its business so that it can be developed. This is a descriptive research which is conducted in field and desk research. The results indicate the green mussel supply chain starts from farmers to distributors then to retailers and to end consumers, while supply chain players manage relationships between supply chain from upstream to downstream and vice versa well. Some of the green mussel business opportunities that are visible include selecting the Longline method to minimize costs and increase profits also suitable for high wave waters, farming is simple and does not require special treatment, lots of green mussel seeds are available in the waters, the profit from one longline is around Rp. 691,667, the location is close to PPI Lempasing (3 km in 8 minutes). In addition to developing the green mussel business, it is necessary to conduct a study that is in line with the government's efforts in formulating a strategy for developing the fishing industry in Bandar Lampung.